Sleep quality and fatigue level, clinical and demographic factors in women with rheumatoid arthritis - Kozłowska, Katarzyna Anna; Bączyk, Grażyna (Frontiers in Global Women's Health, 2025)
BackgroundSleep, as one of the factors influencing people's lives, strongly impacts the standard of living of RA (rheumatoid arthritis) patients. The study aimed to determine the level of sleep quality in RA women and whether fatigue and selected demographic and clinical factors influence it.MethodsThe study included 110 female patients diagnosed with RA. Sleep was assessed using The Pittsburgh Sleep Quality Index (PSQI), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) was used to evaluate fatigue, and a proprietary questionnaire was used to assess demographic and clinical factors.ResultsMost women had low sleep quality (>5 points)—71.1% of people. Poor sleep quality in older people (p = 0.0123) and married patients (p = 0.0367). Poor sleep quality was also influenced by pain (p = 0.0006), morning stiffness (p = 0.0002), DAS28 (p = 0.0367), and feeling of fatigue (p < 0.0001). In multiple and logistic regression analysis, pain was the main factor contributing to poorer sleep quality.ConclusionAssessment of factors influencing sleep quality that influence RA patients’ well-being is very important. Determining which factors affect the quality of life will allow them to be controlled and mitigated. Our research has shown that pain is primarily responsible for reducing sleep quality.